Influence of daily free time spent outside in a paddock and stable management on behavioural disturbances and health in the horse - Eklund, Annika (2009)
"People involved with horses must understand causes and effects of behaviours, why they arise, their cost and benefits, if they truly are undesirable behaviours and in that case to whom and in the end how to best treat them without reducing the horses quality of life"(Cooper and Mason 1998).